Determinants of performance of supplemental immunization activities for polio eradication in Uttar Pradesh, India: social mobilization activities of the Social mobilization Network (SM Net) and Core Group Polio Project (CGPP) - Weiss William M; Rahman Md Hafizur; Solomon Roma; Ward Dora (BMC Infectious Diseases, 2013)
Abstract Background The primary strategy to interrupt transmission of wild poliovirus in India is to improve supplemental immunization activities (SIAs) and routine immunization coverage in priority districts. The CORE Group, part of the Social Mobilization Network (SM Net), has been successful in improving SIA coverage in high-risk areas of Uttar Pradesh (UP). The SM Net works through community level mobilisers (from the CORE Group and UNICEF) and covers more than 2 million children under the age of five. In this paper, we examine the reasons the CORE Group had been successful through exploration of which social mobilization activities of the CORE Group predicted better performance of SIAs. Methods We carried out a secondary data analysis of routine monitoring information collected by the CORE Group and the Government of India for SIAs. These data included information about vaccination outcomes of SIAs in CORE Group areas and non-CORE Group areas within the districts where the CORE Group operates, along with information about the number of various social mobilization activities carried out for each SIA. We employed Generalized Linear Latent and Mixed Model (GLLAMM) statistical analysis methods to identify which social mobilization activities predicted SIA performance, and to account for the intra-class correlation (ICC) between multiple observations within the same geographic areas over time. Results The number of mosque announcements carried out was the most consistent determinant of improved SIA performance across various performance measures. The number of Bullawa Tollies carried out also appeared to be an important determinant of improved SIA performance. The number of times other social mobilization activities were carried out did not appear to determine better SIA performance. Conclusions Social mobilization activities can improve the performance of mass vaccination campaigns. In the CORE Group areas, the number of mosque announcements and Bullawa Tollies carried out were important determinants of desired SIA outcomes. The CORE Group and SM Net should conduct sufficient numbers of these activities in support of each SIA. It is likely, however, that the quality of social mobilization activities (not studied here) is as or more important than the quantity of activities; quality measures of social mobilization activities should be investigated in the future as to how they determine vaccination performance.